Extrusion of brewers' spent grains and application in the production of functional food. Characteristics of spent grains and optimization of extrusion. Issue 4 (15th August 2017) - Ivanova, Kristina; Denkova, Rositsa; Kostov, Georgi; Petrova, Todorka; Bakalov, Ivan; Ruscova, Milena; Penov, Nikolay
Abstract : Brewers' spent grains (BSG) form 85% of the waste products from the brewing process. BSG contain a number of substances with functional benefits and can be used for the production of new food types. The present publication considers the main characteristics of BSG derived from six malt types: light barley malt, Pilsner malt, wheat malt, Munich malt type II, Vienna malt and Carafa malt type III. The spent grain starch content, the degree of starch gelatinization, the phenolic compound content and the antioxidant capacity of the spent grains were examined. Based on the values of the latter three parameters, optimization of a malt mixture was performed, which guaranteed BSG with a maximum total phenolic compound value and maximum antioxidant capacity. It was found that the type and the conditions for malt production influenced the physicochemical composition of brewers' spent grains. Copyright © 2017 The Institute of Brewing & Distilling